Dosage Regimens for Meropenem in Children with Pseudomonas Infections Do Not Meet Serum Concentration Targets. Issue 2 (20th November 2019) - Hassan, Hazem E.; Ivaturi, Vijay; Gobburu, Jogarao; Green, Thomas P.
Abstract : There have been literature reports that some recommended meropenem dosage regimens may fail to meet therapeutic targets in some high‐risk children and adults. We evaluated this observation in children using literature studies conducted in infants and children. Observed and, as necessary, simulated data from the literature were combined, yielding a data set of 288 subjects (1 day to ~ 17 years). A population pharmacokinetic model was fit to the data and then used to simulate the recommended dosing regimens and estimate the proportion of subjects achieving recommended target exposures. A two‐compartment model best fit the data with weight, postnatal age, gestational age, and serum creatinine as covariates. The US Food and Drug Administration (FDA)‐approved dosing regimens achieved targets in ~ 90% or more of subjects less than 3 months of age for organisms with minimum inhibitory concentration (MIC)'s of 2 and 4 mg/L; however, only 68.4% and 41.7% of subjects older than 3 months and weighing < 50 kg achieved target exposures for organisms with MIC's of 2 and 4 mg/L, respectively [Correction added on January 23, 2020, after first online publication: "> 3 months" corrected to "less than 3 months".]. Moreover, for subjects weighing more than 50 kg, only 41.3% and 17% achieved these respective targets. Simulation studies were used to explore the impact of changing dose, dosing interval, and infusion duration on the likelihood of achieving therapeutic targets in these groups. Our findings illustrate that current dosing recommendations for children over 3 months of age fail to meet therapeutic targets in an unacceptable fraction of patients. Further investigation is needed to develop new dosing strategies in these patients.